2019
DOI: 10.1088/1361-6463/ab4ba7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted abatement of SF6 in a dielectric barrier discharge reactor: investigation of the effect of packing materials

Abstract: The greenhouse gas hexafluoride (SF6) and its degradation is a research hotspot in the environmental field. In a double-layer dielectric barrier discharge reactor, the degradation process of SF6 was studied when packed in glass beads or γ-Al2O3 pellets as well as with no packing system. The results show that the packing materials changed the physical characteristics of the discharge, increasing the equivalent capacitance and discharge power and leading to the generation of more active particles and high-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This trend is consistent with Cui et al, higher degradation efficiency can be obtained as pulsed voltage increases, but more energy will be lost in thermal energy and light energy, which leads to lower energy yield in the degradation process. [ 37 ] Furthermore, the gas flow rate is also considered the key factor affecting the SF 6 degradation process. Figure 7a shows that the degradation efficiency decreased with the increase in gas flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is consistent with Cui et al, higher degradation efficiency can be obtained as pulsed voltage increases, but more energy will be lost in thermal energy and light energy, which leads to lower energy yield in the degradation process. [ 37 ] Furthermore, the gas flow rate is also considered the key factor affecting the SF 6 degradation process. Figure 7a shows that the degradation efficiency decreased with the increase in gas flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental setup has been described in our previous study [12] and is shown in Figure 1. In this experiment, the discharge frequency is maintained at 8.5-9.0 kHz and input power is controlled within 100 W. We selected argon (Ar) as the background gas for SF 6 dilution due to its promotion effects on the discharge and SF 6 degradation [21].…”
Section: Experimental Setup and Degradation Parametersmentioning
confidence: 99%
“…In 2019, we studied the influence of the packing material type on SF 6 degradation in a packed bed DBD (PB‐DBD) and found that both glass beads and γ‐Al 2 O 3 pellets could promote the degradation efficiency. Additionally, γ‐Al 2 O 3 packing could change the SF 6 degradation pathway and regulate the product selectivity [12].…”
Section: Introductionmentioning
confidence: 99%
“…As pre-heating temperature increases, some products changed significantly. However, [41] pointed out that the temperature changes below 400 °C would not influence SF 6 degradation. Therefore, the mechanism for the temperature effect on the products is still unknown.…”
Section: Products Analysismentioning
confidence: 99%